Thermal energy storage : systems and applications - Dinçer, İbrahim, 1964- author.; Rosen, Marc (Marc A.), author. 501578 (Hoboken, NJ : Wiley, 2021)
"The ability of thermal energy storage (TES) systems to facilitate energy savings, renewable energy use and reduce environmental impact has led to a resurgence in their interest. Thermal Energy Storage Systems and Applications, Third Edition has been comprehensively updated to cover new models, methods and approaches in thermal energy storage. It includes new case studies and new thermal management systems and applications and covers integrated systems with energy storage options. Design, analysis and assessment criteria are considered and environmental impact and sustainability is covered. New tools in exergy and extended exergy are also covered"--